Microwave assisted alkali pretreatment of fruit peel wastes for enzymatic hydrolysis - TIWARI, GARIMA; SHARMA, ABHISHEK; DALELA, MANU; GUPTA, RISHI; SHARMA, SATYAWATI; KUHAD, RAMESH CHANDER (The Indian Journal of Agricultural Sciences, 2017)
The present study proved the potential of generating reducing sugars from various fruit peel wastes (pineapple, mango, orange) using microwave assisted alkali pretreatment. The results showed that enzymatic hydrolysis of pretreated pineapple peel waste produced maximum reducing sugar, i.e. 0.774 g/g dry biomass. X-ray diffraction study revealed the prominent role of microwave heating in the disruption of recalcitrant lignocellulosic structures and improving the enzymatic digestibility of FPWs. We believe that microwave assisted alkali pretreatment of FPWs could be an energy-saving technology aimed to valorize the agro-industrial wastes in a cost effective way.